Hubungan Persepsi Pengembangan Karier Dengan Kinerja Karyawan PT. Jaya Tama Inovasi Agro Indonesia - Henny Pratiwi; Sinaga, Kalvin; Riyadh, Muhammad Ilham (CV. Utility Project Solution, 2023)
This study aims to determine the relationship between perceptions of career development and the performance of . Jaya Tama Inovasi Agro Indonesia employees. The population of this study were employees in 3 fields, namely the education administration section, the marketing administration section and the work placement administration, totaling 55 people. The research sample uses a saturated sample system where the total population is used as a sample in the study. This study uses one scale, namely the career development perception scale. While the employee performance scale of the documentation method was taken in the HRD section of the . Jaya Tama Inovasi Agro Indonesia. On the career development perception scale consists of 4 aspects, namely responsibility, position status, authority, and compensation and employee performance scale is work quantity, work quality, work attendance and work timeliness. Data collection uses one psychological scale, namely the Career Development Perception Scale ( 40 items were declared valid with a value of r count > r table (0.3) and all items were declared reliable with a Cronbach alpha value of 0.916). The results of this study showed a correlation coefficient rxy 0.778 with p = 0.000 (p <0.01). These results indicate that the hypothesis put forward by researchers is that there is a positive relationship between perceptions of career development and the performance of . Jaya Tama Inovasi Agro Indonesia employees. The positive correlation coefficient value indicates that the direction of the relationship between the two variables is positive, meaning that the more positive the perception of career development, the better the performance of the . Jaya Tama Inovasi Agro Indonesia employees. Perceptions of career development make an effective contribution of 60.6% to the performance of . Jaya Tama Inovasi Agro Indonesia and 39.4% are influenced by other factors not examined in this study.